2013
DOI: 10.1111/ajpy.12018
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of the Levels of Emotional Awareness Scale

Abstract: The Levels of Emotional Awareness Scale (LEAS) is a performance-based measure of emotional awareness. This study examined whether the LEAS is suitable to be administered orally by administering two half-forms of the LEAS to literate participants; one orally and one in written format. In doing so, this study raised questions regarding the internal reliability and statistical equivalence of the LEAS half-forms. Despite this, results showed no significant difference between oral and written administration. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…The LEAS was administered orally by trained interviewers and audio-recorded. Roberton et al (2020) found no difference between the LEAS scores in dependence on the administration mode (oral vs. written). The interviewers were instructed not to ask follow-up questions (e.g., “But how would you feel?” in case of reported thoughts) or reinforce patients’ responses in any manner.…”
Section: Methodsmentioning
confidence: 67%
“…The LEAS was administered orally by trained interviewers and audio-recorded. Roberton et al (2020) found no difference between the LEAS scores in dependence on the administration mode (oral vs. written). The interviewers were instructed not to ask follow-up questions (e.g., “But how would you feel?” in case of reported thoughts) or reinforce patients’ responses in any manner.…”
Section: Methodsmentioning
confidence: 67%
“…Oral administration has been shown to be a reliable option when there are literacy limitations in a study’s sample (Catania et al, 1990). A previous study that compared methods (written vs. oral) of administration of another psychological measure found no significant differences in their internal reliability and statistical equivalence (Roberton et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, oral administration of these measures has not been previously validated. However, prior research with other psychological measures indicated that method of administration (written vs. oral) does not affect general test performance in adults (Roberton, Daffern, & Bucks, 2013).…”
Section: Methodsmentioning
confidence: 95%
“…In certain contexts, a participant's ability to write or type may not adequately capture their ability to conceptualize and describe emotion. An oral version was developed for use in prisoners and found to correlate adequately with the written version (Roberton et al 2013). Further study is needed to determine if the social context of oral administration systematically affects scores in certain contexts (e.g., social phobia or other psychopathology).…”
Section: Description Of the Scalementioning
confidence: 99%